(untitled) (Research, Society and Development, 2025)
Copaiba oil extracted from Copaifera spp., has been increasingly studied for its therapeutic benefits, including wound healing, anti-inflammatory, and anti-tumor properties. In a previous study, we demonstrated the positive impact of copaiba oil on skin wound repair in rats, notably enhancing lesion contraction and dermal annex approximation. However, despite its therapeutic potential, further toxicological evaluations are necessary to understand the safety of prolonged exposure to copaiba oil, particularly at low doses. To address this gap, the current study aimed to assess the effects of topical copaiba oil treatment on hematological, biochemical profile, and histopathological exams in male Wistar rats with surgical wounds. Forty-eight male Wistar rats with surgically induced skin wounds were randomly distributed into two groups (n=24): one group was treated with copaiba oil, while the other received mineral oil as a control. Topical treatments were administered once daily for a period of 21 days following the creation of the surgical wounds. Hematological and biochemical analyses revealed no significant alterations attributable to copaiba oil treatment. Similarly, histopathological evaluation of the heart, liver, and kidneys showed no evidence of tissue damage or morphological changes. These findings support the safety of topical copaiba oil, indicating it promotes wound healing without inducing systemic toxicity or hematological disturbances in rats.